An Omani Visitor in Ḥimā: Insights Into Connections During the Hellenistic Era - Prioletta, Alessia; Arbach, Mounir (Arabian Archaeology and Epigraphy, 2025)
ABSTRACT This study presents a new epigraphic inscription from Ḥimā (Najrān, Saudi Arabia), which records the arrival of an individual from ʿUmān during the reign of Abīyathaʿ Ghaylān, king of the Amīr tribe. Written in a South Arabian script but showing non‐Ancient South Arabian—possibly Hasaitic—linguistic features, the inscription provides rare evidence of trans‐Arabian mobility and diplomatic relations during the Hellenistic period. By contextualizing this text alongside other inscriptions and coins from southern and eastern Arabia, the article explores the political role of Abīyathaʿ, the integration of the al‐Asd tribe and the significance of long‐distance networks involving Gerrha and Mleiha. A newly discovered graffito referencing the gentilic Ġr‐ite also contributes to ongoing debates on the ancient name of Gerrha. The use of regnal and Seleucid‐era dating in these inscriptions offers further insight into evolving chronological systems across pre‐Islamic Arabia.
Keywords: Archéologie -- Oman

Simulation hydraulique des écoulements dans un canal d’irrigation de la fin du IVe millénaire en Oman - Bertrand-Krajewski, Jean-Luc; Pouzol, Tanguy; Brochier, Jacques Elie; Baudet, Robinson; Castel, Corinne (Techniques Sciences Méthodes, 2025)
Une mission archéologique pluridisciplinaire conduite par Corinne Castel, sous l’égide du CNRS, de l’Université Lyon 2 et du Ministry of Heritage and Tourism of Oman, mène des fouilles au Sultanat d’Oman depuis 2019 sur le secteur d’Al-Arid. Ce secteur est situé sur la rive gauche du wadi Khuwaybah, dans une large vallée au pied des monts Al-Hajar, à une quinzaine de kilomètres au nordouest du site archéologique de Bāt classé au patrimoine mondial de l’Unesco. Les fouilles ont mis en évidence deux phases principales d’occupation du site d’Al-Arid au début de l’âge du Bronze, aux périodes Hafit (environ 3200-2700 avant notre ère) puis Umm an-Nar (environ 2700-2000 avant notre ère). Elles ont révélé un nombre remarquable de vestiges : sept tours, une nécropole, des bâtiments, un atelier de transformation du minerai de cuivre en métal de la période Hafit.
Keywords: Archéologie -- Oman; Irrigation -- Oman

Qalhat, A Medieval Port City of Oman. From a field of ruins to UNESCO - Chung-To, Guillaume (Bulletin critique des Annales islamologiques, 2025)
Keywords: Archéologie -- Oman

Hinterland Monuments of Ancient Nomads - Roman, Garba (The archaeological heritage of Oman, 2025)
This book presents the first dedicated study of the enigmatic 2000-year-old trilith monuments in Southeastern Arabia, revealing their geographical extent, chronological range, and cultural significance. Based on an analysis of 921 trilith sites comprising almost four thousand clusters. the book identifies four distribution hotspots across Yemen and Oman, extending the known chronology of triliths back to 410 BCE. Statistical analyses suggest that triliths played a role in mobility and rituals for safe passage, pre-Islamic water rites, and rituals associated with ancestor cults. A spatio-temporal analysis has traced the migration patterns of populations linked to trilith monuments, revealing their spread from southern Oman in the 5th century BCE to eastern Oman by the 1st century BCE, before retreating southwards in possible connection with the semi-historical migration of the Azd tribes. The book concludes that triliths were multifunctional spaces rather than structures built for a single purpose. Two topical chapters describe the relocation of a trilith to the National Museum in Muscat and the challenges involved in identifying trilith monuments using remote sensing. This book will serve as an invaluable reference volume for scholars working on the stone monuments of Arabia. It contains a repository of extensive data that is essential for understanding ancient nomadic societies in southern Arabia.
Keywords: Archéologie -- Oman

Excavations and Surveys of 2022 and 2023 at Wadi al-Maʻawil (Oman) - Kzzo, Ahmed Fatima; Ludovico, Alessandro Di; Ramazzotti, Marco (Sapienza Università Editrice, 2025)
During 2022 and 2023, our field activities focused on Wadi al-Maʻawil, a very large wadi close to the Muslimāt village in between Nakhal and Afī oasis, where in 2022 we discovered a completely unexplored and multifaceted ecotope. We selected a 10 x 10 Km squared area encompassing this ecotope after ground truthing because of the high intensity of the archaeological features and because it featured three adaptive conditions: the presence of large widyān with central terraces, the presence of an anthropized oasis and the presence of a possible ancient settlement pattern in which the anthropic features (settlements, graves, pathways) were almost close together and intervisible. This volume studies the landscape of the site and classifies, studies, and describes all the finds during the excavations and survey campaigns of 2022 and 2023.
Keywords: Archéologie -- Oman

The karst landscape of the Dhofar Mountains (Sultanate of Oman). Landforms and human exploitation at the edge of the Indian Ocean Monsoon - Zerboni, Andrea; Pezzotta, Andrea; Azzoni, R. S.; Cremaschi, Mauro (2025)
4
Keywords: Archéologie -- Oman

The role of tectonics and river network in shaping the landscapes of the Sultanate of Oman - Pezzotta, Andrea; Zucali, M.; Al Kindi, Mohammed Hilal; Zerboni, Andrea (2025)
4
Keywords: Archéologie -- Oman

Seals in the Early Iron Age "1300-300 B.C.E." in the Oman Peninsula: Case Studies from Salut in Bahla and Dibba Al-Baiya’ah in Musandam - Alawi, Reem Mohammed Said al- (Sultan Qaboos University, 2025)
Keywords: Archéologie -- Oman

A rural perspective on the Umm an-Nar and Wadi Suq periods from Burj Huraiz (northern Oman) - Olijdam, Eric; Düring, Bleda; Vreeze, Michel de; Litsenburg, Zoe van (Proceedings of the Seminar for Arabian Studies, 2025)
Despite substantial research on the Umm an-Nar (c.2700–2000 BC) and Wadi Suq (c.2000–1600 BC), our understanding of rural settlements and their economies during these periods remains limited. Research on the Umm an-Nar period has focused mainly on large sites and monumental towers, and relatively few vernacular buildings have been excavated. Similarly, the few known Wadi Suq-period settlements have provided scant insights into their nature. The discovery of a series of rural settlements in the northern Bāṭinah, particularly the well-preserved vernacular buildings of the Umm an-Nar and Wadi Suq periods at Burj Huraiz in the 2018 season of the Wadi al Jizzi Archaeological Project (WAJAP) survey and subsequent excavations in 2023–2024, have resulted in new and intriguing data. The main results from these excavations are presented here and contextualized, thereby enhancing our understanding of rural settlements in the Umm an-Nar and Wadi Suq periods.
Keywords: Archéologie -- Oman

The production of Bahlā Ware in the context of late Islamic Oman - Živković, Jelena; Lopez, Jose Carvajal; Döpper, Stephanie; Biezeveld, Irini (Proceedings of the Seminar for Arabian Studies, 2025)
Among glazed Arabian Gulf wares, Bahlā Ware stands out as one of the most documented objects of consumption at sites in Oman, the UAE, Qatar, and Bahrain from the sixteenth to the early twentieth century. Previous scientific studies of Bahlā Ware from UAE and Qatar formed the basis for understanding its production technology and provenance, as well as the unique composition of its lead-barium glaze. This paper presents the new results of petrographic and chemical analyses of thirty-two Bahlā samples from Oman, contributing to a better understanding of the compositional variability of ceramics, the provenance of raw materials, and techniques used for the application of lead-barium glazes. The compositional match between samples of Bahlā Ware from Oman, the UAE, and Qatar reveals the exploitation of the same geological source of raw materials over several centuries. Previous research has associated this source with the ophiolitic geological formation in Oman. The results of chemical analysis of glazes confirmed that the Omani samples were also coated with a lead-barium glaze of the same type as reported for UAE and Qatar.
Keywords: Archéologie -- Oman; Céramique -- Oman

The first collective Neolithic megalithic tomb in Oman - Danielisová, Alžběta; Maiorano, Maria Pia; Šneberger, Jiří; Ackerman, Lukáš; Daněček, David; Garba, Roman; Martinez-Garcia, Alfredo; Lüdecke, Tina (Antiquity, 2025)
, A newly discovered grave in Wadi Nafūn, Oman, features a unique burial structure, combining monumental architecture and the collective deposition of human remains from multiple Neolithic groups. Detailed analysis of the burial community reveals new insights into Neolithic rituals and subsistence strategies during the Holocene Humid Period in southern Arabia.
Keywords: Archéologie -- Oman

Archaeometallurgy in northern Oman—Diachronic copper production on a smelting site in Wadi al-Salh - Bukowski, Krzysztof; Pieńkowska, Agnieszka; Woronko, Barbara; Moska, Piotr; Kiersnowski, Hubert; Piestrzyński, Adam; Ghafri, Waleed Awabh Harib Said al- (Archaeometry, 2025)
Archaeometallurgical studies at the Salh site in northern Oman have provided new data on copper technology in the Bronze Age and Islamic periods. Archaeological results indicate that it may have functioned seasonally. Slag analyses have shown possible technological changes over the centuries. Smelting was carried out under reducing conditions, using oxidized copper ores weathering zone deposits. The scale of copper production at Salh1 was relatively small in both periods, but—due to its strategic location near important trade routes—the site could have functioned as part of a short-range as well as long-range mercantile network.
Keywords: Archéologie -- Oman

Modern Architectures vs ‘Pre-Modern’ Ḥārāt: Architecture Against the Tribes in Oman - Delitz, Heike (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

#Mudbrick #Oman: On the Tourist Perception of Abandoned Ḥārāt Architecture - Kanditt, Josephine; Schmidt-Lux, Thomas (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Tourisme -- Oman; Urbanisme -- Oman

Harat Al ʿAqr in Nizwa and Three Artistic Traditions - Bandyopadhyay, Soumyen; Briguglio, Claudia (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Reclaimed, Rediscovered or Reinvented – The Changing Perceptions of Ḥārāt since the Omani Nahḍa - Mershen, Birgit (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Documentation of Omani Traditional Settlements (Ḥārāt): Reality and Aspirations - Mahrooqi, Ali Bin Hamood al- (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Memory and Belonging in the Bat Oasis, Oman - Young, Ruth; Brooks, Alasdair (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Life Histories of Mudbrick Settlements in Central Oman - Döpper, Stephanie; Biezeveld, Irini (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered - Döpper, Stephanie; Mershen, Birgit; Kanditt, Josephine; Biezeveld, Irini; Schmidt-Lux, Thomas (Sidestone Press, 2025)
Caught between the poles of remembering and forgetting, glorification and neglect, the abandoned mudbrick settlements (ḥārāt) of Oman are a vital object of conflicting processes of interpretation and negotiation. Adopting a diachronic perspective, the multi-disciplinary book’s chapters examine their past, present and future. The book presents approaches and results of archaeological, ethnographic, historical and sociological research on abandoned ḥārāt. Oman’s landscape is dotted with abandoned mudbrick settlements and quarters, known as ḥārāt, either isolated in the countryside or surrounded by vibrant, modern urban centres. Most of them were abandoned during the economic upturn and opening of the country after Sultan Qaboos bin Said came to power in 1970. People’s move from traditional mudbrick to modern concrete houses led to the deterioration and decay of the physical substance of the mudbrick buildings. In the face of these conditions, various Omani and international actors have repeatedly warned against the uncontrolled loss of this valuable cultural heritage. The former inhabitants of the mudbrick houses and their descendants have also repeatedly emphasised their emotional attachment to these abandoned places and their personal significance to them. At the same time, others, especially tourists, have glorified the dilapidated state of the ruins as an aesthetically beautiful backdrop for a romanticised vision of the past. This was the starting point for the interdisciplinary research project “The abandoned mudbrick settlements of central Oman: Between romanticisation and neglect”, funded by the Gerda Henkel Foundation as part of the “Lost Cities” programme between 2020 and 2022, and conducted by the editors of the present volume. It constitutes the proceedings of the closing conference of the project, in which team members present their results and leading experts give their input on inhabited, abandoned and re(dis)covered mudbrick settlements in the Sultanate of Oman.
Keywords: Architecture -- Oman; Archéologie -- Oman; Urbanisme -- Oman

Time of magan (2022-23): The ras al jinz project, excavation & survey - Azzarà, Valentina M.; De Rorre, Alexandre P. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The project is focused on exploring the Neolithic and Early Bronze Age (EBA) occupations of Ras Al Jinz RJ-3. This site remained un touched until recent excavation efforts by Time of Magan, revealing that during the Umm an-Nar period, RJ-3 likely constituted a part of a larger settlement in conjunction with RJ-2, situated across the bay. Findings from five seasons of excavation suggest not only the existence of craft-centred zones during this era, but also evidence of earlier settlements associated with daily life. The project’s goal is to gather new information from these settlements, thereby highlighting the way of life of southeastern Arabian communities. The study of village life, social interactions, activity organisation, and economic diversification at the community level, will provide new insights into the factors that led to the EBA complexification, and will help determining the influence of local and foreign contributions. Fur thermore, the excavation of RJ-3 concludes a comprehensive series of investigations into the EBA occupations of the bay, illuminating a pivotal complex where both settlement evidence and funerary remains have been meticulously examined. New explorations in the bay will also contribute to the museumification of Ras Al Jinz and support its nomination for inclusion in the UNESCO Heritage List.
Keywords: Archéologie -- Oman

Omani-polish archaeological mission 2022: Excavations at QA20 and QB2 in the qumayrah micro-region - Bieliński, Piotr; Pieńkowska, Agnieszka; Szymczak, Agnieszka; Iskra, Mateusz (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
During the 6th season of investigations, the Omani-Polish expedition researched previously unexcavated sites in the micro-region of Qumayrah in the Al Hajar Mountains: QA 20, located near Ayn Bani Saydah, and QB 2, near the village of Bilt. The exploration at QB 2 uncovered a substantial Umm an-Nar settlement, offering insight into its layout and architecture, despite the challenges of removing layers of stone rubble. Additionally, the preliminary documentation of a round stone structure, likely of Umm an-Nar origin, was undertaken at QB 6. QA 20, an Iron Age II hilltop site, revealed an unexpectedly advanced organisation of space, resembling urban planning more than a rural settlement, challenging previous assumptions.
Keywords: Archéologie -- Oman

Project VirtuHalban (2023): Italian anthropological mission for the heritage of arabia - Bortolini, Eugenio; Benazzi, Stefano (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Project VirtuHalban investigates an Early Bronze Age funerary site at Halban, on an elevated coastal terrace where the Al Batinah coastal plain meets the Hajar Al Gharbi mountain ridge. These well-preserved monumental tombs, some reaching heights of over four metres, are significant markers of their era. Research suggests that the Halban tombs may span two distinct periods: the Hafit period (c. 3100-2600 BCE) and the Umm an-Nar period (c. 2600-2100 BCE), indicating a transition in tomb design during the Bronze Age. The project also investigates building techniques and materials employed in tomb construction, potentially having cultural or chronological significance. Excavation of tomb HAL021 during the 2023 season yielded valuable insights into its contents, including small beads and human remains, providing potential clues about the people buried in the tomb and their cultural practices. To enhance documentation, the researchers used 3D/virtual recording techniques, allowing for precise spatial mapping and the creation of 3D models and panoramas.
Keywords: Archéologie -- Oman

Archaeological mission at bat/al arid (MBA mission): 2023 season (4th season) wilāyā of ibri (dhahirah governorate) - Castel, Corinne (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The project aims at enriching the debate on the nature of the settlement sites, the emergence of socio-economic complexity and the human-environment relationships in the Southern foothills region of Oman in the Early Bronze age. It is based on an extensive survey, a geoarchaeological and hydrological study in the region comprised between Al Arid and Bat (UNESCO site), and excavations at the recently discovered site of Al Arid (15 km NW of Bat). The approach is holistic and interdisciplinary and relies on specialists from the CNRS and universities, post-doctoral researchers and students. The team is composed of archaeologists, geoarchaeologists, hydrologists, biological anthropologists, geophysicist, archaeobotanist, specialists of pottery (formal typologies, physico-chemical and petrographic analyses of pastes), Geographic Information Systems and photogrammetry. After four seasons of work, we know that Al Arid was inhabited during two main phases: in the Early Bronze age and the Late Islamic period. In the Bronze age, the site appears as a regionally important centre. The discoveries are varied and sometimes exceptional: 7 towers concentrated on 25 ha, a material, local and exogen, including a superb copper alloy axe; from the beginning of the Bronze Age it seems: a copper metallurgical workshop, a canal for diverting the course of the wadi and 99 Hafit-type tombs among them two have been excavated ; dated to the Umm an-Nar period: a settlement sector (including a house that has been completely excavated), 9 tombs. These discoveries allow us to consider that communities lived there, on a recurrent, if not permanent basis, very early in history, relying on irrigation, a mastery of copper technology and exchanges with the coastal region and Mesopotamia. The mission is also heavily involved in the protection and enhancement of the region’s heritage, working alongside the Ministry of Heritage and Tourism on the Visitor Centre project of Bat.
Keywords: Archéologie -- Oman

Bologna university project in the sultanate of oman (2023): Fieldwork activities at al khutm and ras al hadd - Cattani, Maurizo; Barchiesi, Francesca; Cavazzuti, Claudio; Cocca, Enzo (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Bologna University has a long tradition of research activities in the Sultanate of Oman, with investigation in the coastal area of Sharqiyah and more recently in the project of Al Khutm tower in the area of Bat (Al Dhahirah Governorate). The fieldwork of the campaign 2022-2023 was carried out at Al Khutm investigating the outer area of the tower characterized by a monumental stone wall. The archaeological complex appears now more valuable with a unique outline of defensive and entangled structures. Several finds, including pottery, softstone and metal, are defining the starting of the construction at the end of 3rd mill. BCE. At Ras Al Hadd the Italian team is currently involved in the excavation of the early 3rd mill. BCE cemetery around the settlement of HD-6. Several clusters of cairns as part of two main cemeteries named HD-7 and HD-10 were identified in previous research. Among dozens of burial structures, the current investigation concerned the group 12 of HD-7 cemetery and three cairns were excavated. The preliminary results show the regional character of cairns with specific size, architectural features and ritual customs.
Keywords: Archéologie -- Oman

French mission “arabian seashores”: The desert project “exploring the omani rub’ al khali” (december 2022) - Charpentier, Vincent; Maiorano, Maria Pia (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The French mission “Arabian Seashores” has been exploring the Omani coast of the Arabian Sea since 2010. The team has prospected, surveyed various sites, and conducted excavations at Khuwaymah, Masirah Island, Hallaniyat Archipelago, Sharbithat, Hasik as well as other sites along the coast. Additionally, they have explored the Jebel Qara and several rock art sites. The mission’s research focuses on the chronology of the Final Paleolithic to the Early Bronze Age, spanning the period between 10,000 and 2000 BCE. Specifically, their attention is on the transition from the Paleolithic to the Neolithic era, marking the shift from predatory societies to the first productive communities. The mission has made significant discoveries, including the Final Paleolithic cave of Natif and the Neolithic sites of Ad-Dahariz (Salalah), Hasik, and Sharbithat. Simultaneously, a project in the Rub’ Al Khali desert was carried out in collaboration with a team of geologists and paleontologists. During the latest mission in December 2022, particular emphasis was placed on research in this area, confirming the extraordinary potential of these sites. The campaign played a critical role in enhancing our understanding of cultural transfer, settling patterns, and technological innovation in Southern Arabia during the Neolithic period. Overall, the project has expanded our current knowledge of Neolithic cultures in desert locations by conducting an integrated study of the paleoenvironment and a techno-quantitative examination of the lithic industries. This work lays the foundation for future research in this field.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Rock art survey - Döpper, Stephanie (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In 2023, a new project on rock art in Eastern Arabia, with special focus on the Al Sharqiyah North Governorate started. It aims at recording the spatial and chronological distribution of rock art as well as its integration into the natural and anthropogenic landscape. In the first field season from February to April 2023, over 4,000 rock art images have been recorded at the sites of Al Tasawir, Lizq, Al Khashbah and Al Rakhi. This encompassed digital sketches of the rock art panels, photography of the individual rock art images, taking of UTM coordinates, and vectorising the photographs on a computer later on. In addition, 3D models of all recorded sites were generated by structure-from-motion (SfM). As a citizen science component of the project, a smartphone application (Rock Art Oman) was developed that allows everyone to support the project by documenting rock art in an easy manner. This does not only provide more data for research but also help to foster the awareness of people in Oman for their rock art heritage.
Keywords: Archéologie -- Oman

Omani-italian archaeological expedition at al tikha (2023) - Douglas, Khaled; Pizzimenti, Sara (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Omani-Italian Archaeological Expedition at Al Tikha, a joint project between the Sultan Qaboos University and the University of Pisa started in 2022 with the aim to investigate the archaeological site of Al Tikha, strategically located in the Batinah plain, near modern city of Al Rustaq. The 2023 excavation season focused on seven distinct areas: settlements (Mound A, Mound B, Building S1, Building S2), a metallurgical site (Mound C), and the necropolis (T1, T2).
Keywords: Archéologie -- Oman

Wadi al jizzi archaeological project 2023 - Düring, Bleda S. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
This paper presents the main results of the 2023 excavations at Site 73 / 66 in the Liwa hinterlands (northern Oman) undertaken by the WAJAP team. Excavations focused on domestic buildings dating to the Umm an-Nar and Wadi Suq period. Here, the buildings and the deposits found within them will be discussed.
Keywords: Archéologie -- Oman

Archaeological landscape and environmental dynamics of duqm and nejd (ARDUQ): Season 2 (2022-2023) - Garba, Roman; Danielisová, Alžběta F.; Rose, Jeffrey I. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In March 2023, an international team of archaeologists, anthropologists and geologists led by the Institute of Archaeology of the Czech Academy of Sciences in Prague successfully completed the second season of the ARDUQ (Archaeological landscape and environmental dynamics of Duqm and Nejd) expedition. Researchers from ten countries took part in fieldwork in two regions of the Sultanate. The first team, based in Duqm (south-central Oman), carried out fieldwork at Nafūn, excavating a Neolithic collective burial and documenting extensive rock art sites, both unique in south-east Arabia. Small test trenches for lithic studies were also carried out. ARDUQ’s investigations reveal a rich archaeological landscape at Duqm with long-term occupation. The second team worked in Dhofar (southern Oman). The team discovered seven Lower Palaeolithic sites in the Rub’ Al Khālī desert, with a high concentration of handaxes. Test trenches on the Nejd plateau revealed stratified Middle Palaeolithic artefacts of Nubian Complex, and samples were taken for optical stimulated luminescence dating. A systematic study of the flint raw material was also initiated. Research at Dhofar will shed new light on the early hominin and anatomically modern human dispersal Out of Africa, a topic of global importance and interest.
Keywords: Archéologie -- Oman

A diamond in the raw in oman (season 2022): Al ṣalaylī archaeological project - Gaudiello, Michela (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
After about 5-year of survey in Al Ṣalaylī valley, conducted by the Heidelberg University team, in November 2022 have started the proper archaeological excavation at the site. The documented archaeological evidence which characterized the site of Al Ṣalaylī, span from the Iron Age to the Late Islamic periods. Despite the high number of hut tombs, may be dated to the (Late?) Iron Age period, the 2022 season of archaeological excavation focused on that area of the site previously labelled “Persian Village”. The excavation confirmed that part of the site was inhabited and exploited during the Islamic period. Due the different typology of structures put in evidence in the partially excavated Trench 1, the area has been renamed as “Settlement / Workshop”. The first season of archaeological excavation was made possible thanks to the Beatrice de Cardi award funded by the Society of Antiquaries of London.
Keywords: Archéologie -- Oman

Italian archaeological research at daba al bayah (2022): Exploration and analysis of burials at the bottom of the LCG-2 tomb - Genchi, Francesco (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The stratigraphic investigations on tomb LCG-2 led to the identification of the phase of use of the tomb floor, which, on the basis of radiocarbon dating and archaeological material, seems to refer to a final phase of Iron Age III. The research of our last exploratory season focused on the continuation of the investigation of this homogeneous phase identified at the base of the corridor. The base is characterized by a clay path running through the centre of the corridor, bordered by elongated pits containing burials and objects and informing us of how the bottom of the structure was used. This contribution focuses on the description of the last burials exposed at the bottom.
Keywords: Archéologie -- Oman

Italian archaeological mission of the university of naples l’orientale in dhofar, oman (2022-2023): Archaeological research at al baleed - Giunta, Roberta; D’Andrea, Andrea (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Italian archaeological mission of L’Orientale in the Dhofar region was established several years ago and has carried out some short surveys and two excavation campaigns (December 2021-January 2022 and December 2022-January 2023). The main objective of the mission is to continue research at the archaeological site of Al Baleed (ancient Ẓafār) –located in the Salalah area, which has been the subject of numerous archaeological investigation since the middle of the last century. The site covers more than 1.5 km × 800 m, but a large part still remains unexplored, and questions concerning its foundation, stratigraphic sequences and the materials that have been brought to light still require in-depth investigation. In order to gain a deeper knowledge of the occupation of the area in the medieval Islamic period, it is considered equally necessary to undertake research and study of the numerous burial spaces in the Salalah area. Within this context, the mission began a survey aimed at documenting the large cemeteries located in the western part of the site of Al Baleed (outside the boundary wall) and at Al Robat, two areas which, on preliminary investigation, appear to preserve the oldest funerary evidence.
Keywords: Archéologie -- Oman

Archaeological water histories of oman (ArWHO) project (2022-23): Iron age settlements and trade in yanqul wilayat - Harrower, Michael J.; Paulsen, Paige (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The ArWHO project’s 2023 season focused on the Iron Age and early Islamic Periods, specifically concentrating on mapping settlement architecture and exploring trade in softstone and copper resources in Yanqul Wilayat. The ArWHO team mapped architecture at four Iron Age sites, discovered an ancient softstone (chlorite) quarry, and tested an autonomous Ground Penetrating Radar system. Additionally, the project engaged local residents by organising a Yanqul Community Archaeology Day to share findings and promote awareness of archaeology. Our work clarifies the histories of ancient societies, their environment, architecture, and trade activities contributing to deeper understanding of the ancient past.
Keywords: Archéologie -- Oman

Khor kharfot research project (2022 & 2023): Wadi sayq, dhofar, sultanate of oman - Hauck, F. Richard (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Beginning in the spring of 2014, the Archeological Research Institute (ARI) has been involved in archaeological investigations in the Khor Kharfot Archaeological Reserve of Dhofar, Oman. A three-year excavation contract was signed with Sultan Qaboos’s advisory council in 2015. In 2022 the excavation permit was granted a five-year renewal with the Omani Ministry of Heritage and Tourism. This article summarizes the efforts of Campaigns 6 and 7 during 2022 and 2023 to expand an appreciation of Wadi Sayq’s ancient environment and its early Paleolithic through Islamic period occupations and extensive architecture. This summary of Campaigns 6 and 7 excavations contains ARI’s recent discoveries at five separate loci: site II-4 (Neolithic and Iron Age occupation site), site IV-1 (Neolithic Kharfot Mound Site), site IV-3 (Neolithic-Iron Age-Islamic Period Alcove Site), site IV-4 (Neolithic Upper Platform), and site IV-5 (Neolithic Walkway).
Keywords: Archéologie -- Oman

Sultan qaboos university project in oman (2022): Discovery of an early bronze age settlement in al ghoryeen, mudhaybi, sultanate of oman - Jahwari, Nasser Said al-; Douglas, Khaled; Hesein, Mohamad (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Department of Archaeology at Sultan Qaboos University (SQU), in collaboration with the Ministry of Heritage and Tourism (MHT), has conducted the 3rd season (December 2022) of intensive excavations at the site of Al Ghoryeen in Wadi Andam region on the southern fringes of the eastern Hajar Mountains in the Northern Al Sharqiyah Governorate of Oman. It was excavated under the direction of Professor Nasser S. Al-Jahwari and Dr Khaled Douglas. Participants included colleagues and MA students from the Department of Archaeology at SQU (Dr Mohamad Hesein, Dr Nasser Al-Hinaei, Yaqoob Al-Rahbi, Yaqoob Al-Bahri, Al-Reem Al-Alawi, Suad Al-Harasi, Wajd Al-Zakwani, Buthainah Al-Ghofaili and Huda Al-Daihani) and the German Archaeological Instiute in Berlin (represented by Dr Kristina Pfeifer). The results of the excavation discovered the first and largest settlement in Oman dating back to the Early Bronze Age of Hafit period (ca. 3400-2700 BC).
Keywords: Archéologie -- Oman

French archaeological mission to central oman (2023): Explorations in bisya - Jean, Mathilde; Sauvage, Martin (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The French Archaeological Mission in Central Oman (FAMCO) studies the diachronic settlement of Bisya, one of the Oman peninsula’s main archaeological zones, in the Hajar mountains foothills. This region, which benefits from a location at the confluence of several wadis and local mineral resources, has been populated since the Paleolithic. It experienced a particularly prosperous development in the Early Bronze Age and the Iron Age. The first aim of the mission is to identify the development of human communities through survey and excavation. The Palaeolithic program investigates the first settlements of the Arabian Peninsula, determining the presence or absence of Neanderthal populations and their relationship to the arrival of modern Homo sapiens between the Lower and Middle Palaeolithic. The central part of the mission focuses on the Early Bronze Age to understand the beginnings of the oasis agrosystem, the domestication of the date palm, the first irrigation systems, the development of monumental domestic and funerary architecture, and the appearance of local crafts (pottery, copper metallurgy). Our research aims to provide new evidence on the role of Oman (Land of Magan in the Mesopotamian texts) within the Middle East during the Bronze Age, particularly its relations with Lower Mesopotamia (Sumerian country), Iran (the region of Fars and Makran) and the Indus Valley.
Keywords: Archéologie -- Oman

ISTIDAMA: The long-term cultural sustainability project (2022-23): Surveys and excavations in tanūf, ad-dākhilīyah governorate - Kondo, Yasuhisa (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Long-Term Cultural Sustainability (ISTIDAMA) Project aims to identify the eco-cultural factors of sustainable lifeways and historical landscapes of the canyons and foothills of the Hajar Mountains. To this end, the project team conducted three field activities: (1) general surveys in the Tanūf district of Ad-Dākhilīyah Governorate, (2) detailed documentation of the cemeteries in the survey area, and (3) excavations at the cave site of Mughārat Al Kahf in Wadi Tanūf. Regarding the general survey, the team documented seven archaeological sites in Wadi Tanūf and six sites in As-Suwaihiriyah in the floodplain of Wadi Al Abyad at 5 km east of Tanūf. Among these, the team documented the cemetery of WTN07, 13, and 14 in detail. These cemeteries were occupied from the Wadi Suq period (ca. 2000 to 1600 BCE) and Early Iron Age (ca. 1300–650 BCE). In the cave site, the team opened a new trench next to the last season’s one to verify stratigraphy. The team also took coprolite, date stone, charcoal, and soil sample for ancient DNA, stable isotope, and radiocarbon dating analyses.
Keywords: Archéologie -- Oman

DHOMIAP project (2022-23): New archaeological discoveries in dhofar - Lischi, Silvia (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The archaeological campaign at Khor Rori made a significant contribution to the understanding of the history and culture of the region. It focused on three main objectives: to increase knowledge of the KR-N1 necropolis, to determine the chronology and function of previously discovered structures, and to understand the land use of the Dhofar Coastal Culture and the Ancient South Arabians. To achieve these objectives, exploratory investigations were carried out in three different structures to determine their chronology, cultural affiliation, and possible use. At the same time, the study of the KR-N1 necropolis continued, with particular emphasis on dolmenic cysts and multiple cist tombs. This excavation provided valuable insights into the chronology, depositional features and mortuary practices of the Dhofar Coastal Culture. In addition, we summarise here the preliminary results of the archaeological campaign at Wadi Andhūr, part of the HELFA programme under the DHOMIAP project. The campaign aimed to explore the archaeologically rich area of Wadi Andhūr. Notable discoveries include confirmation of the South Arabian origin of the site DMa0610 and an inscribed stone of South Arabian origin. Further research is needed to answer questions about the site’s chronology, use and links with other settlements.
Keywords: Archéologie -- Oman

Ichtyophagoi, their culture and economy: Survey and excavation in wadi bani khalid (WBK1, aqr zaida al athri) and tiwi - Loreto, Romolo (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Project’s activities in the Sultanate of Oman, Ash-Sharqiyah North region, are directed towards the study of the Iron Age in northern Oman, in order to investigate those historical cultures known as fish-eating communities (Ichtyophagoi) from Greco-Roman sources and locally defined as Early to Late Iron Age cultural facies. From 2014 to 2018 the project focused on the study of the seasonal coastal economy of northern Oman in the Iron Age, in particular the phases of the 1st millennium BCE, between Qurayat and Ras Al Hadd, including Bamah and Tiwi as main coastal sites. Since 2018, the joint project has extended the area of research to urban oases further inland, along the Al Hajar mountain range, to define the settlement strategies between the Iron Age and the advent of Islam. These seasonal villages were in fact part of a complex socio-economic network involving the urban and agricultural oases in the interior, located along the Al Hajar mountain range, possessing their own hunting/fishing, farming and livestock economies, acted as bridges for trade between the coasts and the more inland regions, between Oman and the Emirates for at least the entire first half of the 1st millennium BCE and from the 1st century BCE to the 4th century CE.
Keywords: Archéologie -- Oman

DExPO project (2022-23): Dolphin exploitation in prehistoric oman - Maini, Elena (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Prehistoric communities along the coasts of southeastern Arabia relied heavily on marine resources. However, dolphin remains in the zooarchaeological record remain poorly understood due to fragmentation, taphonomic changes, limited osteological collections, and the lack of a specific methodology for determination. In response to these challenges, the DExPO project aimed to develop a protocol for the analysis of osteological data from odontocetes and cetaceans from Late Neolithic and Early Bronze Age sites in central Oman. Agreements with the Ministry of Heritage and Tourism along and support from the Natural History Museum of Oman facilitated the project. Initial implementation took place in a pilot project (2019-2020) on cetaceans in the NHM collection, and has been extended to analyse archaeological remains from key sites in Ash-Sharqiyah Governorate. Ongoing objectives include developing a methodology for identifying and documenting archaeological dolphin remains and applying these methods to large osteological collections. This is central to the study of dolphin hunting and exploitation strategies, combining zooarchaeological, material culture and environmental data, using ethnographic parallels and experimental approaches. Through the DExPO project, the enigmatic relationship between prehistoric communities and marine mammals is gradually being unravelled, providing insights into their ancient coexistence along the coasts of the Arabian Sea.
Keywords: Archéologie -- Oman

First research activities at the prehistoric mountain site hayl ajah at the inner flank of al jabal al kawr - Mateiciucová, Inna; Wilding, Maximilian (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
As the first undertaking of its kind, Project SIPO has embarked in 2018 on the environmental-archaeological research of a lithic site in Oman in a true mountain ambient – Hayl Ajah (a large sediment-filled depression at 1019 m a.s.l. on an intermontane karst plateau between Al Jabal Al Kawr and Al Jabal Al Ghul; Figs 1 and 2). Because porous karstic limestone – other than more compact rocks – allows the infiltration of precipitation water into the matrix of the rock itself, our project aims to find out, whether during prehistoric periods a degree of water storage inside limestone rock-layers and aeolian surface sediments could have made good for the reduced precipitation in the northern part of Oman compared to the country’s south. Judging from the archaeological finds, the site Hayl Ajah and similar smaller sediment places in the surroundings mountains have been accessed by people during different prehistoric periods (probably since the Middle Palaeolithic, definitely during the Neolithic and Umm an-Nar period). At the present stage we encounter various kinds of small, dispersed water and sediment features in our research area that could have served mobile foragingpastoral groups while roaming the bleak mountain landscape. Indicative of this is the remarkably wide spectrum of mostly non-local raw materials used for the stone artefacts of Hayl Ajah. For some of the lithics encountered at the mountain site, yet no real analogy to lithic traditions in other parts of the Arabian Peninsula can be found. Other stone artefacts, according to first OSL/C14 dates, belong to a time period when aridization was under way (Late Neolithic). From this evidence we infer tentatively that mountainous places in Al Jabal Al Hajar have had significance for prehistoric humans during past dry periods - perhaps as the “roof section” of an environmentally diversified, yet integrated refugium in the Kawr-Akhdar Area encompassing the more open alluvial places at the mountain front (cf. Uerpmann, Uerpmann & Jasim 2000).
Keywords: Archéologie -- Oman

La trobe archaeological research in oman: The archaeology of out of africa dispersal events in oman (2019-2022) - Meredith-Williams, Matthew; Fitzpatrick, Dianne (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The debate on the timing and nature of “Out of Africa” dispersals of multiple waves of the genus Homo has been based on a limited number of securely dated sites; the majority of the Palaeolithic archaeological record for Arabia is represented by undated surface sites. This project aims to contribute to the body of knowledge and debate through targeted field survey for stratified Palaeolithic sites that can be well dated. A multidisciplinary team of geologists, geomorphologists, hydrologists, dating experts and archaeologists has been assembled to specifically target this question. Our first three survey seasons in 2019, 2020 and 2022 gave invaluable insights into the landscape setting of Oman which have fed directly into the later seasons. Preliminary results include a number of surface sites with material typologically linked to the Lower, Middle and Upper Palaeolithic of Oman, and a small number of stratified sites have been identified and are currently undergoing analysis.
Keywords: Archéologie -- Oman

Archaeological exploration of fulayj near saham in the north batinah governate (2016-23) - Priestman, Seth; Jahwari, Nasser Said al-; MacDonald, Eve; Kennet, Derek (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Fulayj Fort Project focuses on the unique archaeological remains at the site of Fulayj: a small, regularly planned, heavily defended, stone-built fortification constructed sometime between the early 5th to mid-6th century AD during the late pre-Islamic period and its subsequently reoccupation during the first decades following the Islamic conquest of Oman in the 7th century (Figs. 1-2). The fourth season of excavation took place over a six-week period from the 10th of January to the 20th of February 2023. It involved the work of an international team with a maximum of ten participants, including specialists from the UK, Oman, Canada, Greece and the Republic of Georgia. We were pleased to host one trainee from the Ministry of Heritage and Tourism regional office of the North Batinah Governate (Fig. 3). Excavation focused on the eastern side of the fort near to the fort entranceway (Fig. 4) with work in the north-east corner extending our understanding of a series of mudbrick rooms associated with the secondary occupation of the fort in the early Islamic period. Further excavations were opened in the south-east corner, and on the fort exterior across the south-east corner tower.
Keywords: Archéologie -- Oman

Archaeological exploration of suhar port in the north batinah governate (2023) - Priestman, Seth; Jahwari, Nasser Said al-; MacDonald, Eve; Kennet, Derek (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Suhar was one of the leading ports in the Indian Ocean during the Abbasid period. With Basra and Siraf, it formed a centre of maritime power in the Gulf and Arabia. The historian and traveller Istakhri, who wrote the Kitab Al-Masalik wa Al-Mamalik, and who lived in the 10th century, tells us that Suhar was the biggest and richest town in Oman. He tells us that it is not possible to find a city more rich in buildings and foreign wares than Suhar, and that many merchants live there who trade in ships with other countries. It is known that merchants came to Suhar from China, India and many other places. It is certain that Suhar is the most important location in Oman for the history of the first centuries of Islam. Archaeological research has already been carried out in Suhar, in the 1970s and 1980s, but there is still much more to learn about this important place. In January 2023 a British and Omani archaeological team led by Seth Priestman visited the town to investigate the remaining archaeological evidence (Fig. 1). A short sur-vey of the town revealed important information about its history. New locations came to light and important new finds of imported Chinese ceramic were made. The British and Omani team is hoping to continue work at Suhar so that the full potential of this important site can be developed.
Keywords: Archéologie -- Oman

Archaeological exploration of seeb (al hail north) in the muscat governate (2022-23) - Priestman, Seth; MacDonald, Eve; Gajewska, Maria (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
"Seeb is the site of an extensive coastal settlement located in the northern suburbs of Muscat. Previous investigations by Romolo Loreto in 2013 indicate the presence of areas of deep stratigraphy, intact occupation deposits and architectural remains covering most phases of the Islamic period. More recently, documentation by the local community has highlighted the exceptional quality of the finds assemblage, with objects drawn from across the Indian Ocean world, often closely comparable to materials from other key urban centres in the region such as Suhar, Samarra or Siraf. The existence of a large urban centre on the southern Batinah remains to be better integrated into our wider historic reconstruction of the medieval topography of Oman. To address this, a three-week field-walking survey, followed by a week of finds processing, was carried out in January-February 2023. It involved mapping and surface collection to augment our understanding of the size, nature, and diachronic development of the medieval settlement. The work was conceived in partnership with the local community, taking the factor of existing interest as the motivating driver in the plan and design of future research. Public workshops, social media and continuing conversations with residents and other stakeholders form important channels in the pursuit of the project."
Keywords: Archéologie -- Oman

Sapienza university of rome archaeological mission in the arabian peninsula and the gulf area (MASPAG): Archaeological explorations in wadi al ma’awel 2022-23 - Ramazzotti, Marco (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Sapienza Archaeological Mission in the Arabian Peninsula and the Gulf Area (MASPAG) surveys in the Omani southern Batinah, southwest of Muscat, near the Muslimat oasis, has recently revealed a new hitherto unknown multi-millennial archaeological landscape crossed by the Tropic of Cancer. In this vast area, two enormous cemeteries with hundreds of collective tombs have been identified. The oldest graves typologically and morphologically date from the end of the 4th millennium, but both the cemeteries appear to be associated with long-lasting settlements continuously inhabited up to the Islamic period. The two cemeteries next to a settlement that was fortified in the Iron Age offer the possibility of investigating the social complexity of those mobile groups interposed between south-eastern Arabia and the Persian Gulf on a broad spectrum. Powerful coalitions capable of governing large portions of the piedmont territory interposed between the rocky Hajar mountains and the spectacular western coasts of the Arabian Sea, a nomadic and half-nomadic territorial state in the south-eastern frontier of the ancient Near East which Mesopotamian texts identify as the Land of Magan.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): UmWeltWandel, paleoenvironmental studies - Schmidt, Conrad; Beuzen-Waller, Tara; Schmitt, Katharina; Reinhardt, Antonia; Proctor, Lucas (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The final field season of paleoenvironmental studies for the UmWeltWandel project lasted from 7 January–17 April 2023. It resulted in the collection of further samples of sediment, rock, charcoal, snail, plant, pollen, and water for laboratory analysis in Germany. More than 70 sedimentological sections were investigated in the vicinity of Al Khashbah to study soil and landscape formation processes. Once completed, these studies will provide important insights into climate and vegetation of the Neolithic and Bronze Age in Central Oman.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Ibra south - Schmidt, Conrad; Kluge, Jonas; Biezeveld, Irini (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
A small, newly discovered Umm an-Nar settlement close to the southern outskirts of the modern city of Ibra was investigated by a team from the University of Frankfurt, Germany between 1 March 2023 and 11 April 2023. The investigation included a detailed surface survey with find collection, as well as small-scale excavations at two of the buildings. The results of the first campaign suggest a well-planned settlement structure with specialized areas for the production or refinement of copper and copper objects. Of particular importance was the discovery of multiple plano-convex copper ingots during the excavations of one of the domestic buildings.
Keywords: Archéologie -- Oman

Archaeological expedition to al khashbah (2023): Al khashbah KHS-a - Schmidt, Conrad; Maiorano, Maria Pia; Proctor, Lucas (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Several locations north of the village of Al Khashbah have yielded Neolithic remains, most likely due to the area’s accessible chert outcrops and elevated fluvial terrace systems overlooking wadi floodplains. KHS-A, the main Neolithic site in the area, is distinguished by extensive flint scatters, isolated stone constructions, and fireplaces. In 2022, the team excavated a preliminary test trench (KHS-A.1) that yielded a high number of lithics and charcoal samples. Radiocarbon dating placed the age of the complex within the Late Neolithic Period. In 2023, further excavations at KHS-A.13 were undertaken with the goal of confirming the age dating of the site and expanding our understanding of the extent and occupational sequence of the KHS-A complex. The trench consisted of a 3 × 4 m exposure revealing multiple fireplaces, ash pits, and post holes. The investigation of the Neolithic occupations at Al Khashbah seeks to open new routes and further perspectives in the study of Early and Middle Holocene in the broad area between the mountains and the Rub Al Khali desert.
Keywords: Archéologie -- Oman

Archaeological investigations on the necropolis of khor jarama: Campaign 2021-2022 - Sévin Allouet, Christophe (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Archaeological campaigns led during these last five years on the necropolis of Khor Jarama, located in the Ja’alan area, has brought to light what is probably a new prehistoric culture unknown in Oman. Indeed, the excavation of seven tombs located not far from the Jarama lagoon has enabled the discovery of the first funerary monuments known to date in Oman. These latter have been dated from the middle of the 4th millennium BCE for the oldest ones, that is to say several centuries before the monumental tombs of Hafit period. These tombs are characterized by new architectures as well as by new funerary practices observed in Oman. This discovery fills a void of data observed until now in Oman and located between 3600 and 3200 BCE, that is to say the period of transition between the end of the Neolithic and the beginning of the Hafit period. This discovery highly changes the vision that we had about the first prehistoric societies in Oman: there is probably here, very early at the end of the Neolithic, structured groups, probably hierarchized, and led by members buried in monumental tombs. A new campaign of survey in the Ja’alan area has allowed the discovery of eight others necropolis showing the same architectural characteristics than tombs of Jarama, and thus belonging probably to this period. Current investigations on these necropolis could come to confirm the identification of a new prehistoric period in Oman.
Keywords: Archéologie -- Oman

Bat archaeological project (2022-2023): Beyond the bat oasis - Swerida, Jennifer; Dollarhide, Eli; Jensen, Reilly; Bryant, Robert (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Bat Archaeological Project conducted its winter field season from December 26, 2022 until March 5, 2023. Our research focused on different areas of the Bat area’s Bronze Age archaeological landscape, including Rakhat Al Madrh, the Khutm Settlement, and the proposed location of the new Bat Visitors Center. At Rakhat Al Madrh, the team excavated three Umm an-Nar period houses. With assistance from a team of geomorphologists and geologists from the Sorbonne University, we also discovered that the houses were located around an ancient marsh/wetland where Umm an-Nar people likely experimented with early agriculture and pastured livestock. This ancient settlement is unlike any other known Early Bronze Age village or town in Arabia because of this environment. At Al Khutm, the team discovered and excavated Umm an-Nar houses and tombs and digitally mapped a very large fortress at the site dating to the Iron Age II. At the proposed location for the new Bat Visitors Center, we excavated and surveyed several mounds, which appear to be tombs that continue from the necropolis across the wadi. With the generous permission of the Ministry of Heritage and Tourism, laboratory analyses on geological, C-14, botanical, and ceramic samples collected this season are currently underway.
Keywords: Archéologie -- Oman

Terraced landscapes of the jabal akhdar (2022-23): Fieldwork at shuraijah and wadi bani habib - Turner, Sam; Zerboni, Andrea; Kinnaird, Tim; Kindi, Mohammed al-; Sevara, Christopher; Brandolini, Filippo; Pezzotta, Andrea (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Agricultural terraces are prominent features in landscapes across the world. Terraces enable the cultivation of steep land for crops including cereals, fruit, vegetables, flowers and trees, and can be irrigated where careful water management is required. They allow the redistribution of sediment to create soils with improved root penetration and water retention. Terraces are highly variable, their regional development reflecting a combination of natural factors (differing geologies, geomorphology, hydrological conditions) and landscape histories (manuring, field management, crop selection, water availability). The histories of terraced landscapes remain poorly understood, including in Oman. Little is known about when they were constructed, and how they were used and developed across different periods and environments. A key reason for this lack of knowledge is that terraces have proven exceptionally difficult to date using conventional or scientific archaeological methods. This research project uses a new method developed by the research team to date terraces in Oman for the first time and use geoarchaeological methods to investigate how they were used in the past. In March 2023, targeted fieldwork in two villages of Jabal Akhdar (Ash Shuraijah and Wadi Bani Habib) allowed collection of sediment samples for dating and geoarchaeological analysis.
Keywords: Archéologie -- Oman

Joint heidelberg university/ministry of heritage and tourism project (2023): Archaeological rescue operation at al khod, ḥūr ad-dabʿ, muscat - Yule, Paul A. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In September 2018 the population of the capital area reached 1.4 million. Places such as Al Khod need room for growth. The development of this area during the past 20 years includes the building of the Nizwa road, highway 15, to its north-east Lulu Al Bandar super market and flanking to its west a large housing settlement. There, pre-Islamic hut tombs are scattered over the three low mountains (600m x 300m area). The Ministry of Defence plan to develop the mountains (Fig. 2) as a recreational facility – the ‘Heritage Hill’ project. This report sketches the mapping and excavation (12.01. to 26.01.2023) and documents 140 burial structures, the excavated finds, the clearance of stone from the tomb cluster on the southern mountain, figures of the 3D and drawings of the tomb images. This site, with its hut tombs and niche graves is important to solve the problem of the dating and nomenclature of prehistoric funerary architecture. The author searches for an alternative to the nomenclature ‘cairn’ which describes not the original architecture, but rather an undifferentiated, dishevelled state of preservation.
Keywords: Archéologie -- Oman

The salut and bisya archaeological mission (2022): The rock art landscape and its threatening - Zerboni, Andrea; Degli Esposti, Michele; Pezzotta, Andrea; Marinoni, Alessia; Gallinaro, Marina (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The geoarchaeological investigation around the Bisya and Salut Archaeological Park disclosed the complexity of local archaeological landscape dating to the last millennia of the Holocene and the main steps in developing sophisticated systems for land exploitation. Recent fieldwork focused on the importance of rock art in the region, which needs to be systematically surveyed and documented. Rock art sites feature various representations dating from the second millennium BCE onwards and the research carried out in 2022 aimed to assess its archaeological potential, as well as identify any threats to its preservation. The investigation confirms that local rock art is a valuable asset for Oman’s archaeology and potential tourism. It suggests the development of geo-cultural tourism routes that combine archaeological sites and rock art with the natural landscapes. Nonetheless, the preservation of rock art and the issues threatening it need careful consideration and assessment for future planning.
Keywords: Archéologie -- Oman

At the Dawn of History: The Late Pre-Islamic Age in South-Eastern Arabia - Yule, Paul A.; Mauro, Fausto (The Archaeological Heritage of Oman, 2025)
This fresh study thoroughly re-casts the unrecognised Samad Late Iron Age (SLIA) and its archaeological context in the 600 years which flank the year 0 CE, providing valuable insights into the significance and complexities of this enigmatic era. Through meticulous research of archaeological sites and recent discoveries, the authors present an in-depth understanding of the SLIA. A particular focus is given to examining the relationship between the SLIA assemblage and that of the Mleiha/PIR, parsing the cultural connections between these separate yet intertwined archaeological phenomena. By investigating diverse topics such as burial practices, pottery, small finds, trade networks and architecture, this work aims to offer a comprehensive grasp of the material culture and historical scene of the centuries preceding the rise of Islam. With its contribution to the ongoing academic discourse on the archaeology of south-eastern Arabia, this book fills a niche for scholars and enthusiasts seeking archaeological knowledge about this fascinating Arabian period.
Keywords: Archéologie -- Oman

A First Glance at Pre-Islamic Pigments in Shells From Salūt (Sultanate of Oman) - Degli Esposti, Michele; Lotti, Paolo; Crippa, Gaia; Diego Gatta, G.; Zerboni, Andrea (Arabian Archaeology and Epigraphy, 2025)
Marine shells containing greenish or blackish pigments are frequently found at pre-Islamic archaeological sites in Southeast Arabia and are generally interpreted as ancient eye makeup, representing a long-standing tradition that continues to the present day. While these ‘cosmetic’ shells are primarily found in funerary contexts, their presence in residential areas suggests broader use within the community. Although relatively abundant, these shells have undergone limited chemical and mineralogical analysis, hindering a deeper understanding of their composition and production. This study presents the first archaeometric results from six marine shells excavated at Bronze and Iron Age sites in the Salūt and Bisya oasis (Sultanate of Oman). Chemical analyses reveal copper- and manganese-bearing minerals as the primary components of the greenish and blackish pigments, respectively. The presence of these minerals near the Salūt oasis suggests local pigment sources. This study represents the first step in a broader analytical programme aimed at the characterisation of samples from other archaeological sites of Southeast Arabia spanning over a wider chronological time frame.
Keywords: Archéologie -- Oman

Al-Nejd, a Fortified Samad Late Iron Age Settlement in Sharqiyya North Governorate, Sultanate of Oman: an Attempted Reconstruction - Yule, Paul A.; Ayash, Nasser Bovoleti (Athīrat: Journal of Ancient Arabia, 2025)
Abstract First reported in 2014, a fortified site atop a small mountain adjacent to the village of al-Nejd shows another facet of the settlements of the little-known Samad Late Iron Age (SLIA). Until recently, few settlements of the Early Iron Age and late pre-Islamic period are recorded and published in the land between the Oman Peninsula (U.A.E.) and Oman’s southern province, Dhofar. While analyzing graves with skeletons and finds of the latter period yields information about their owners, settlements lag far behind. With this background, al-Nejd offers new insight into the settlement, in addition to the first coin to be found in Oman. The authors attempt graphic documentation to contextualize the architecture and answer two questions. First, is there a typical kind of SLIA fortification separate from other periods? Second, how closely is the SLIA related to its neighbors and the preceding period in terms of material culture and architecture?
Keywords: Archéologie -- Oman

New Rock Art Discoveries in Aṣ Ṣafiyya (Wadi Nafūn, Duqm), Sultanate of Oman - Fossati, Angelo E.; Garba, Roman (Athīrat: Journal of Ancient Arabia, 2025)
Abstract The Nafūn rock art complex, located in al-Wusṭā Governorate in south-central Oman, was discovered in 2020 and has emerged as one of the most extensive rock art sites in southeast Arabia. The site features 59 flat limestone rock surfaces with over 200 South Arabian inscriptions and over 500 engraved figures. These figures include maritime animal depictions such as sea turtles, sperm whales, squid, jellyfish, ray fish, and mola mola, along with more common depictions of camels (sometimes ridden) and horsemen hunting oryx or wild canids. The rock art tradition in the Nafūn area is estimated to reach from the 5th millennium BCE to the 2nd millennium CE, offering a unique window into a way of life that endured for over 6,000 years.
Keywords: Archéologie -- Oman

Bronze Age to Early Iron Age Water Harvesting and Management in the Ancient Oasis of Salūt (Bisya, Sultanate of Oman) - Degli Esposti, Michele; Cremaschi, Mauro; Zerboni, Andrea (Open Quaternary, 2025)
During the 3rd millennium BC, a series of oases located along the western foothills of the al-Hajar Mountains saw the establishment of intensive human occupation, associated with the construction of large buildings (the so-called “towers”) and residential structures. These settlements were supported by the onset of agriculture and their development was often associated with and made possible by the introduction of substantial water management systems, including simple wells and complex, large ditches. The oasis of Salūt, near Bisya in the central Sultanate of Oman, is one such Early Bronze Age (EBA) centre. There, extensive investigation of ancient hydraulic structures provided an opportunity to study contexts preserving significant information on ancient climate change and water availability, from the late 3rd to the second half of the 1st millennium BC. A geoarchaeological investigation targeted the huge ditch surrounding the EBA stone tower of Salūt-ST1. Its complete layout was revealed and large portions were fully excavated, allowing the documentation of its infillings and the geological substratum. At the same time, wells excavated at the bottom of the ditch witness the attempt to cope with the lowering water table at the turn of the 3rd millennium BC. Exploration of Iron Age (IA) wells, paired with the geoarchaeological study of sediments from the plain, further extended the chronological scope of the research, while a survey of the area identified ancient and more recent underground and open-air channels, including the exceptional radiometric dating for the introduction of the aflaj (the local term – plural – for the underground water tunnels) network serving the oasis in the late Holocene. This contribution presents the first synthesis including fresh data on how water was harvested and managed in the area of Salūt over almost two millennia, with a diachronic approach that finds little parallels in the region.
Keywords: Archéologie -- Oman